2015
DOI: 10.1007/s10853-015-8822-6
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the luminescence of carbon dots by doping nitrogen element and its application in the detection of Fe(III)

Abstract: Carbon dots (CDs) attract great interests from scientists for their low toxicity and biocompatibility properties and their important applications in the fields of photocatalysts, batteries, bio-images and supercapacitors. Most strategies of making CDs contain several steps, which can be a time-consuming and costly procedure. In this study, nitrogen-doped CDs have been prepared by a onestep hydrothermal strategy with sodium citrate and ethylenediamine as precursors. It is found that fluorescence intensity of CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(25 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…S2 † for comparison), which could be attributed to the homogeneous surface structure, and monodispersity of the CeCDs. 44,45 In addition, the average uorescence quantum yield (QY) of the CeCDs in aqueous solution at room temperature was measured to be 27% using quinine sulfate as a reference (QY of quinine sulfate is 54% at 350 nm excitation wavelength), which is comparable with that in the previous reported CDs. 46 However, the QY of the Ce-free bare CDs was only 13%, lower than that of the CeCDs.…”
Section: Characterization Of Cecdssupporting
confidence: 73%
“…S2 † for comparison), which could be attributed to the homogeneous surface structure, and monodispersity of the CeCDs. 44,45 In addition, the average uorescence quantum yield (QY) of the CeCDs in aqueous solution at room temperature was measured to be 27% using quinine sulfate as a reference (QY of quinine sulfate is 54% at 350 nm excitation wavelength), which is comparable with that in the previous reported CDs. 46 However, the QY of the Ce-free bare CDs was only 13%, lower than that of the CeCDs.…”
Section: Characterization Of Cecdssupporting
confidence: 73%
“…Thus they have shown great potential in bioimaging [3][4][5], photocatalysis [6], electrocatalysis [7], and chemical sensing [8][9][10][11]. In 2004, CDs were first discovered accidentally during the separation and purification of single-walled carbon nanotubes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Group IV NIR QDs is a special kind of QDs which contain only one element. Among them, the research of synthesis and application of CDs received the most attentions . Lin et al reported NIR emissive CDs (683 nm) capable of excitation with a NIR femtosecond pulse laser.…”
Section: Properties Classification and Preparations Of Nir Qdsmentioning
confidence: 99%